Decision-Making Processes in University Study Program Selection: Evidence from a Student Tutoring Program in Jember - Putri, Riris Widiyanti; Zuriah, Nurul; Poerwanti, Endang (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the decision-making processes of senior high school students participating in the Student Study Group (SSG) tutoring program in Jember, Indonesia, with a particular focus on rural educational contexts. The study aims to examine students’ understanding of study program selection, identify influencing factors and challenges, and analyze the role of tutoring in supporting university choice. Employing a mixed-methods explanatory sequential design, quantitative data were collected from 27 twelfth-grade students using structured questionnaires, followed by qualitative data from open-ended responses, interviews, focus group discussions, and document analysis. The findings indicate that most students demonstrated a clear understanding of the importance of aligning personal interests and talents with their academic choices, reflecting relatively high levels of career decision self-efficacy and readiness for higher education. Internal factors, particularly interest, talent, and self-confidence, emerged as the strongest influences on decision-making, while external factors, such as parental support, peer encouragement, and guidance from schools and tutors, played reinforcing roles. Nevertheless, limited access to information on job prospects, difficulty differentiating similar study programs, and parental pressure were identified as major obstacles. The study highlights the significant contribution of the SSG tutoring program in providing both academic guidance and psychological support, enabling students to make more informed and confident decisions. These findings highlight the importance of integrating tutoring-based interventions into comprehensive educational and career guidance systems to promote equitable access to higher education in rural areas.